Prevalence of HDV, HCV, and HIV Infection in the Population of Patients Infected with HBV in a Romanian Cohort - Antoanela Curici; Olivia Mioara Ilie; Dana Elena Mindru (Microorganisms)
Hepatitis B virus (HBV) infections remain a significant global health challenge, especially in low- and middle-income countries where access to healthcare services is often limited. This study aimed to assess the prevalence of hepatitis B virus (HBV), hepatitis delta virus (HDV), hepatitis C virus (HCV), and human immunodeficiency virus (HIV) co-infections in a cohort of 426,528 patients tested for HBsAg in Romania between 2018 and 2023. Of the 17,082 HBsAg-positive individuals (4.0% prevalence), the highest HBV positivity rates were observed in the 30–39 and over 60 age groups. Chronic HBV infection was identified in 13.2% of the cohort, with 3.6% testing positive for HBeAg, indicating active viral replication. Co-infection rates were 11.3% for HDV, 1.4% for HCV, and 0.45% for HIV. The incidence of HDV co-infection increased significantly from 2018 to 2023, particularly in older populations. HCV co-infection was more prevalent in individuals aged 50–59 and over 60, with a declining trend from 2020 onward. The study also revealed a weak correlation between liver enzyme levels (ALT and AST) and HBV viral load, suggesting that liver function tests may not fully reflect the severity of HBV infection. HIV co-infection was notably rare compared to other regions, likely due to regional healthcare interventions. The findings from our study highlight the need for targeted interventions, particularly for high-risk groups such as older adults and middle-aged individuals, to reduce the burden of chronic HBV and its complications.